Apolipoprotein CIII deficiency protects against atherosclerosis in knock-out rabbits - Yan, Haizhao (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVES: Apolipoprotein CIII (apoCIII) mediates the metabolism of triglyceride (TG)-rich lipoproteins. High levels of plasma apoCIII are positively correlated with the plasma TG levels and increase the cardiovascular risk. However, whether apoCIII is directly involved in the development of atherosclerosis has not been fully elucidated. APPROACH AND RESULTS: To examine the possible roles of apoCIII in lipoprotein metabolism and atherosclerosis, we generated apoCIII knockout (KO) rabbits using zinc finger nuclease technique. On a normal standard diet, apoCIII KO rabbits exhibited significantly lower plasma levels of TG than those of wild-type (WT) rabbits while total cholesterol and HDL-cholesterol levels were unchanged. Analysis of lipoproteins isolated by sequential ultracentrifugation revealed that reduced plasma TG levels in KO rabbits were accompanied by prominent reduction of VLDLs and intermediate-density lipoproteins (IDLs). In addition, KO rabbits showed faster TG clearance rate after intravenous fat load than WT rabbits. On a cholesterol-rich diet, KO rabbits exhibited constantly and significantly lower levels of plasma total cholesterol and TG than WT rabbits, which was caused by a remarkable reduction of β-VLDLs, the major atherogenic lipoproteins. β-VLDLs of KO rabbits showed higher uptake by cultured hepatocytes and were cleared faster from the circulation than β-VLDLs isolated from WT rabbits. Both aortic and coronary atherosclerosis was significantly reduced in KO rabbits compared with WT rabbits. CONCLUSIONS: These results indicate that apoCIII deficiency facilitates TG-rich lipoprotein catabolism and therapeutic inhibition of apoCIII expression may become a novel means not only for the treatment of hyperlipidemia but also for atherosclerosis.